Integrative analysis of metabolite and transcriptome reveals biosynthetic pathway and candidate genes for eupatilin and jaceosidin biosynthesis in Artemisia argyi - Lee, Suhyeon; Won, Hyo Jun; Ban, Seunghyun; Park, Yun Ji; Kim, Sang Min; Kim, Hyoung Seok; Choi, Jaeyoung; Kim, Ho-Youn; Lee, Jae Hoon; Jung, Je Hyeong (Frontiers in Plant Science, 2023)
Artemisia argyi (A. argyi) is a medicinal plant belonging to the Asteraceae family and Artemisia genus. Flavonoids abundant in A. argyi are associated with anti-inflammatory, anticancer, and antioxidative effects. Eupatilin and jaceosidin are representative polymethoxy flavonoids with medicinal properties significant enough to warrant the development of drugs using their components. However, the biosynthetic pathways and related genes of these compounds have not been fully explored in A. argyi. This study comprehensively analyzed the transcriptome data and flavonoids contents from four different tissues of A. argyi (young leaves, old leaves, trichomes collected from stems, and stems without trichomes) for the first time. We obtained 41,398 unigenes through the de-novo assembly of transcriptome data and mined promising candidate genes involved in the biosynthesis of eupatilin and jaceosidin using differentially expressed genes, hierarchical clustering, phylogenetic tree, and weighted gene co-expression analysis. Our analysis led to the identification of a total of 7,265 DEGs, among which 153 genes were annotated as flavonoid-related genes. In particular, we were able to identify eight putative flavone-6-hydroxylase (F6H) genes, which were responsible for providing a methyl group acceptor into flavone basic skeleton. Furthermore, five O-methyltransferases (OMTs) gene were identified, which were required for the site-specific O-methylation during the biosynthesis of eupatilin and jaceosidin. Although further validation would be necessary, our findings pave the way for the modification and mass-production of pharmacologically important polymethoxy flavonoids through genetic engineering and synthetic biological approaches.